Phytoremediation for water quality improvement: A sustainable strategy for pollutant mitigation in the North China Plain - Jiang, Baiyang; Doh, Shu Ing; Suryati, Sulaiman; Abdul Syukor, Abd Razak (Penerbit UMP, 2025)
This study focuses on the safety assessment of industrialised buildings in China. Given the marked differences in safety risks between industrialised and traditional buildings, this paper uses a literature analysis method to identify factors affecting the safety of industrialised buildings. These risk factors are further verified through interviews and questionnaires. Using the Analytic Hierarchy Process (AHP), this research establishes a safety rating framework that analyses the impact of people, materials, machinery, technology, management, and environment on the safety of industrialised buildings and assigns appropriate weights to these factors. The findings suggest that management plays a critical role in the success of industrialised building projects and that environmental factors, although less considered in current practice, also have an impact on the safety of industrialised buildings. There are some differences in the importance attached to these criteria by professionals from different backgrounds, and therefore the management of safety in industrialised buildings needs to take sufficient account and balance the perspectives and needs of different stakeholders.